Subconjunctival Hemorrhage as a Sign of Intraocular Retinoblastoma Progression to Orbital Retinoblastoma - Jatikusuma, Anas; Lutfi, Delfitri; Cahyadi, Andi; Heriyawati (Vision Science and Eye Health Journal, 2025)
Introduction: Retinoblastoma is the most common intraocular malignancy of childhood. While treatable when detected early, a delayed diagnosis can lead to orbital extension, which significantly worsens the prognosis. We report an unusual case in which a subconjunctival hemorrhage signaled the progression of intraocular retinoblastoma to orbital involvement. Case Presentation: A 2-year-4-month-old child presented with a one-month history of left-eye leukocoria. Ocular ultrasound and computed tomography (CT) confirmed features of an intraocular retinoblastoma (Group E), and urgent enucleation was planned. The surgery was delayed by two months; shortly before the operation, the child developed an inferonasal subconjunctival hemorrhage that rapidly expanded. During enucleation, a reddish-brown extrascleral tumor was discovered beneath the hemorrhage, indicating orbital extension. Histopathology revealed Grade 3 retinoblastoma with optic nerve invasion (resection margin free of tumor). Adjuvant chemotherapy was initiated postoperatively. Conclusion: Subconjunctival hemorrhage can be an unusual warning sign of orbital tumor extension in retinoblastoma. This case highlights the importance of raising awareness and reducing diagnostic delays, particularly in resource-constrained settings.